Rituximab Induced Pulmonary Edema Managed with Extracorporeal Life Support. (17th January 2018) - Miller, Jacob R.; Isakow, Warren; Masood, Muhammad F.; Aguilar, Patrick; Sanfilippo, Kristen M.; Balsara, Keki R.; Itoh, Akinobu
Abstract : Though rare, rituximab has been reported to induce severe pulmonary edema. We describe the first report of ECLS utilization for this indication. A 31-year-old female with severe thrombotic thrombocytopenic purpura developed florid pulmonary edema after rituximab infusion. Despite advanced ventilatory settings, she developed severe respiratory acidosis and remained hypoxemic with a significant vasopressor requirement. Since her pulmonary insult was likely transient, ECLS was considered. Due to combined cardiorespiratory failure, she received support with peripheral venoarterial ECLS. During her ECLS course, she received daily plasmapheresis and high dose steroids. Her pulmonary function recovered and she was decannulated after 8 days. She was discharged after 23 days without residual sequelae.